COVID-19: a neoliberal nirvana? - Watermeyer, Richard (Critical criminology, 2022)
The COVID-19 pandemic has profoundly impacted the operation of universities around the world. A transition to online platforms and remote forms of working as a consequence of national lockdown measures and campus closures has produced new labour challenges for academic faculty. This article makes use of 12 months of reporting from the academic trade press related to the experience of the pandemic in the UK higher education sector. Accounts published within Times Higher Education signpost the accelerating and accentuating effects of COVID-19 as it relates to universities’ neoliberalization; corporate managerialism within UK universities; and academic work precarization and work-based inequities.